MECHANISTIC UNDERSTANDING OF THE REGULATION OF LUNG RESIDENT MEMORY T CELLS INDUCED BY TB VACCINATION STRATEGIES - Haddadi, Siamak (My University, 2018)
In the recent years, it has been well established that primary respiratory viral infection-induced lung resident memory CD8 T cells (TRM) characterized by the expression of integrins CD49a and CD103, as well as the early-activation marker CD69, constitute the first line of defense against reinfection. On the other hand, viral vector-based respiratory mucosal (RM) vaccination, as well as parenteral vaccination followed by airway luminal manipulation induce lasting and protective lung T cell immunity towards pulmonary tuberculosis (TB). However, it remains poorly understood whether and how these TB vaccination strategies induce TRM in the lung. As such, within this thesis we will investigate generation of lung CD8 TRM upon different TB vaccination strategies and the underlying mechanisms regulating establishment of such cells. Here using distinct models of replication-deficient adenoviral vector-based TB vaccination, we find that RM vaccination leads to generation of lung CD8 TRM identified by the expression of CD69, CD103, and very late activation Ag 1 (VLA-1). These TRM-associated molecules are acquired by CD8 T cells in distinct tissues. In this regard, VLA-1 is acquired during T cell priming in draining mediastinal lymph nodes (dMLNs) and the others acquired after T cells entered the lung. Once in the lung, Ag-specific CD8 TRM continue to express VLA-1 at high levels through the effector/expansion, contraction, and memory phases of T cell responses. We also reveal that VLA-1 is not required for homing of these cells to the lung, but it negatively regulates them in the contraction phase. Furthermore, VLA-1 has a negligible role in the maintenance of such cells in the lung. Separately, we have observed that while parenteral intramuscular vaccination alone does not induce lung CD8 TRM, subsequent RM inoculation of an Ag-dependent, but not a non-specific inflammatory agonist induces lung CD8 TRM. Such generation of lung CD8 TRM needs CD4 T cell help. These findings not only fill the current knowledge gap, but also hold important implications in developing effective vaccination strategies towards mucosal intracellular infectious diseases such as acquired immunodeficiency syndrome (AIDS), TB and herpes virus infection.
Keywords: Lung tissue-resident memory CD8 T cells, Viral vector TB vaccine, respiratory mucosal vaccination, parenteral prime-local pull vaccination